Model Pemberdayaan Ekonomi Umat Berbasis Masjid dalam Meningkatkan Kesejahteraan Masyarakat: Studi Kasus Mesjid Quba Kota Sorong - Mohammad Umar Sisin; Hasbiah Hasbiah; Rokhimah Rokhimah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze mosque-based economic empowerment models in improving community welfare in Sorong City, Southwest Papua. The research employed a qualitative method with a case study approach focusing on Al-Akbar Grand Mosque, Quba Mosque, and Raodah Mosque. Data were collected through observation, in-depth interviews, and documentation involving mosque administrators, program managers, and community beneficiaries. The findings reveal that Al-Akbar Grand Mosque implements a business facilitation-based empowerment model by providing business spaces for Micro, Small, and Medium Enterprises (MSMEs) through the productive utilization of mosque assets. Quba Mosque applies a productive philanthropy-based empowerment model by utilizing zakat, infaq, sadaqah, and donations to support business capital, education, healthcare, and other social needs of the congregation. Meanwhile, Raodah Mosque has not yet implemented a structured economic empowerment program due to limitations in human resources, funding, and institutional capacity, despite having considerable potential for development. The study further indicates that these empowerment programs have contributed positively to improving economic access, strengthening social protection, and enhancing relationships between mosques and the community. However, most programs remain focused on providing access and distributing assistance, limiting their effectiveness in fostering sustainable economic independence. This study concludes that mosques possess significant potential as centers of community economic empowerment; however, optimizing their role requires stronger institutional capacity, improved human resources, and the development of sustainable productive economic programs.